2023
DOI: 10.1002/app.53588
|View full text |Cite
|
Sign up to set email alerts
|

Effect of glass fiber loading and reprocessing cycles on the mechanical, thermal, and morphological properties of isotactic polypropylene composites

Abstract: In this study, a preliminary finding is carried out to obtain the optimum E-glass fiber content in polypropylene (PP) plastic products using loadings of 5, 10, 20, 30, and 40 wt%. The formulation with the optimum loading of 10 wt % glass fiber was reprocessed 10 times via extrusion and compression molding techniques to simulate actual recycling and impacts on service life properties such as mechanical, toughness, chemical, thermal, composition, and morphology. In the result, mechanical properties were lost aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…Then the ILSS, flexural strength and compression strength of the carbonized sample at room temperature were tested to roughly evaluate its mechanical properties. Through the study of the mechanical properties and damage mechanism of the carbonized sample after static ablation of the composites, further understand the ablation enhancement mechanism of the composites 40,41 . It can be seen from Figure 9b,d that the mechanical properties of the composites are significantly reduced after static ablation.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Then the ILSS, flexural strength and compression strength of the carbonized sample at room temperature were tested to roughly evaluate its mechanical properties. Through the study of the mechanical properties and damage mechanism of the carbonized sample after static ablation of the composites, further understand the ablation enhancement mechanism of the composites 40,41 . It can be seen from Figure 9b,d that the mechanical properties of the composites are significantly reduced after static ablation.…”
Section: Resultsmentioning
confidence: 96%
“…Through the study of the mechanical properties and damage mechanism of the carbonized sample after static ablation of the composites, further understand the ablation enhancement mechanism of the composites. 40,41 It can be seen from Figure 9b,d that the mechanical properties of the composites are significantly reduced after static ablation. After the introduction of MP, the ILSS and flexural strength of the cracked carbon/phenolic composites were increased to varying degrees.…”
Section: Characteristics and Ablation Properties Of Fiber-reinforced ...mentioning
confidence: 94%
“…These are mainly composites filled with various types of fibers, mainly glass fibers (so-called short and long fibers and, in a growing number of applications, continuous fibers). In the literature, many examples can be found of the analysis of the impact of recycling or of the use of recycled materials to obtain new polymer materials [ 4 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. The innovative approach in this publication is the analysis of the influence of adding recyclate from pre-consumer waste streams, with the aim of obtaining a mixture of the original polymer with re-granulates and glass fibers not previously subjected to recycling.…”
Section: Introductionmentioning
confidence: 99%
“…In these studies, mostly mechanical properties such as impact, shear stress, and tensile stress was analyzed and investigate with the different binders. 15,16 The studies of various binders has been reported such as biodegradable polymers, 17 polyethylene, 18 epoxies, 19,20 polypropylene, [21][22][23] polybutylene adipate-co-terephthalate, 24 polyamide PA 11, 25 and so forth. In most of the studies, different compatibilizers and plasticizers were used to improve the mechanical properties of binders.…”
Section: Introductionmentioning
confidence: 99%